2016
DOI: 10.1111/obr.12381
|View full text |Cite
|
Sign up to set email alerts
|

The relation between sleep duration and sedentary behaviours in European adults

Abstract: SummaryToo much sitting, and both short and long sleep duration are associated with obesity, but little is known on the nature of the relations between these behaviours. We therefore examined the associations between sleep duration and time spent sitting in adults across five urban regions in Europe. We used cross-sectional survey data from 6,037 adults (mean age 51.9 years (SD 16.4), 44.0% men) to assess the association between self-reported short (<6 h per night), normal (6-8 h per night) and long (>8 h per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
64
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 35 publications
14
64
2
1
Order By: Relevance
“…Consequently, the sleep duration was a proxy measure as non‐wear time at night, which may have overestimated sleep time. Nonetheless, our results are consistent with other studies in children and with a study with European adults, where short sleepers (<6 hours per night) spent more minutes per day sitting in front of screens (computer or tablet) than normal sleepers (6‐8 hours per night) . Thus, our findings could support that those women with fibromyalgia that show more ST spend more time in screen behaviors (computer, tablet, or television) and, therefore, have a shorter sleep duration.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the sleep duration was a proxy measure as non‐wear time at night, which may have overestimated sleep time. Nonetheless, our results are consistent with other studies in children and with a study with European adults, where short sleepers (<6 hours per night) spent more minutes per day sitting in front of screens (computer or tablet) than normal sleepers (6‐8 hours per night) . Thus, our findings could support that those women with fibromyalgia that show more ST spend more time in screen behaviors (computer, tablet, or television) and, therefore, have a shorter sleep duration.…”
Section: Discussionsupporting
confidence: 92%
“…It is well documented that Blacks have earlier chronic disease onset, greater disease severity and shorter life expectancy than Whites (Anderson et al, 2008; Arias, 2007; Bibbins-Domingo et al, 2009; Hertz et al, 2005). A plethora of previous work has also consistently demonstrated that adequate sleep duration and morning type is associated with better health behaviors (Kanerva et al, 2012; Lakerveld et al, 2016; Patterson et al, 2016) and outcomes (Anujuo et al, 2015; Jackowska & Steptoe, 2015; Merikanto et al, 2013). That Blacks are significantly more likely than Whites to be morning type, but less likely to have adequate sleep duration, suggests a complex paradigm between race/ethnicity, sleep and health.…”
Section: Discussionmentioning
confidence: 92%
“…The hypothesized underlying mechanisms include thermoregulation, hunger hormone regulation changes, and/or an impact on physical activity and sedentary behaviors [4952]. Short sleep duration was associated with other lifestyle-related behaviors, such as TV or computer use [52, 53], a correlation between time spent sleeping, physical activity and sedentary behavior was documented [54]. High leisure time physical activity and intake of vegetables were associated with lower prevalence of overweight.…”
Section: Discussionmentioning
confidence: 99%